Curiosity as a Depolarization Strategy: Political Discourse, Group Identity, and the Ethics of Listening in Contemporary Democracy - Hudallah Hudallah; Rifqi Rifqi (Penerbit Hellow Pustaka, 2025)
This article aims to analyze the role of curiosity as a psychological and ethical strategy in overcoming political polarization and enhancing the quality of democratic discourse. This study employs a qualitative method with a literature review approach, analyzing recent empirical findings from political psychology—specifically the research of Todd Kashdan and colleagues—as well as theoretical reflections on public discourse and the ethics of listening. The results of the study indicate that the primary barrier in cross-partisan political conversation is not merely differences in viewpoints, but rather misunderstandings regarding the level of intellectual openness within one’s own group (in-group misperception). Curiosity is proven to be positively associated with openness, intellectual humility, and reduced social distance between political groups. Furthermore, simple psychological interventions that correct perceptions of internal group norms are capable of increasing curiosity and the quality of political interaction. This article concludes that curiosity and the practice of empathetic listening are essential foundations for depolarization and the strengthening of discourse ethics in contemporary democracy.